BATHYMETRY CHANGES ANALYSIS IN SERANG DISTRICT WATERS CAUSED BY SEABED SAND EXPLOITATION - Guntur Adhi Rahmawan; Semeidi Husrin; Joko Prihantono (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2017)
Morphological changes. i.e. shoreline change and bathymetry change of Serang District were significantly influence by natural factors as well as human activities of sand mining (seabed sand exploitation). Bathymetric data were obtained through direct bathymetry measurements using Single-Beam Echosounder (Echotrac CVM Teledyne Odom Hydrographic) and GPS- Real Time Kinematic (RTK) as well as through secondary data from digitization data of DISHIDROS and LPI BIG. The data obtained is then processed to obtain the volume of moved bed sediment using 2 different topography overlays, from the bathymetry analysis result, we obtained the volume of natural sediment transported is 95,800 m3 with the value of average thickness is 0.036 m. therefore, the volume which is caused by human factors (sand mining activities during 2003-2013) is 5,578,470 m3 with the sand mining area extents of 261.9 Ha. Resulting the small basin with 2.13 m depth.  Keywords: bathymetry, lontar village, morphology, sand mining,                            coastal zone